Effectiveness of Using Barcode Scanner-Based Student Attendance to Improve Student Discipline at Madrasah Aliyah Assalafiyyah Mlangi - Ratna Rosita Pangestika; Manik, Yuni Mariani; Rinjani, Afifah Qodri; Muhanik, Farah Mufti; Isnawati, Dian; Puspitaningrum, Yuliastuty (ITScience (Information Technology and Science), 2024)
Based on a preliminary study conducted by researchers, the use of attendance technology utilizing a barcode scanner at MA Assalafiyyah Mlangi has been in place since 2020. The researchers are interested in examining whether barcode scanner-based attendance is effective in improving student discipline. Therefore, they plan to conduct a study entitled The Effectiveness of Barcode Scanner-Based Student Attendance in Enhancing Student Discipline at Madrasah Aliyah Assalafiyyah Mlangi, The method used in this research is a quantitative approach. The subjects of this research were all students of Classes X, XI and XII MA Assalafiyyah Mlangi. The sample used was 70 students from the entire population. The sampling technique uses simple random sampling. Data collection techniques use questionnaires interviews, and documentation. Validity testing was carried out using Pearson product moment with reliability testing values ??using Cronbach's Alpha (?). Data were analyzed using linear regression analysis using the SPSS 22.0 for Windows program. The research results show that: barcode scanner based attendance (X) is effective and has a significant influence on student discipline (Y), which is reflected in the t count of 10.983 with a significance level of 0.000. The barcode scanner based presence coefficient value is 0.923 Based on these values, it can be concluded that attendance using a barcode scanner system is effective in improving student discipline at MA Assalafiyyah Mlangi. Barcode scanner-based attendance is effective in increasing student discipline with a high discipline percentage of 90%, Barcode scanner makes it easier for its users, both students, teachers and employees at MA Assalafiyyah.